Educação geográfica, estética e epistemologia anticolonial - Santos, Gilson Silva (2022)
The present work starts from the thesis that epistemological changes define structural constructions for geographic knowledge; thus, we organize anti-colonial epistemological knowledge focused at Brazilian geographic education from the struggles of black and indigenous people. The thesis starts from the historical reality in the present time and proves that the political, economic, cultural and educational structure is originated from slavery and still maintained as a slave society in other guises and aesthetics, yet still an oppressive, racist, sexist and violent society against black, indigenous people and the working class. The colonial definition and limits were presented directly as an opposition to any overcoming of the daily ills of the working class that lives and is organized by the ruling class in a racist slave-holding structure. The anti-colonial struggle, therefore, had as its principle the rupture with any form of domination and oppression that could be organized by colonizing scientific knowledge and, with that, the founder of a Geography linked to the objectives of capitalism and imperialism. The importance of this thesis lies in the anti-colonial epistemological organization aimed at gnosiological construction that breaks with the oppressive capitalist structure and can, in the daily life of school knowledge, list issues beyond the curricular limits offered for geographic education arising from the needs of the Brazilian ruling class. The rescue of anti-colonial theorists is the decisive point of this work, since African and Latin American revolutionaries proved to be decisive for the composition of an epistemological organization that can be carried out in the school daily life; thus, the theoretical and methodological background starts from a dialectic that breaks with the structure through theories that have as centrality the contestation of violence and the power of the ruling class. The contribution of this work is in the construction of an anti-colonial aesthetics and epistemology that fights directly against all forms of oppression and can constitute a path to a geographic education that strives for the permanent expansion of democracy and human rights, through the confrontation of racism, to sexism and all forms of oppression. The path of these questions came from the epistemological critique of colonized Geography, which cannot see the slavery structure that makes up the national space and, therefore, presented a rupture that can be constituted through the anti-colonial dialectic that definitively starts from the working class, anti-racism and the anti-capitalism resulting in an anti-colonial geographic education organized by the working class that needs to overcome the slave-holding national space. Thus, the present thesis enabled the construction and proof of the need to work with the aesthetically anti-colonial narrative in the Geography of Brazil.